(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: The lipid profile among women with polycystic ovary syndrome (PCOS) is influenced by both insulin resistance and hyperandrogenism. The association of lipid profiles in metabolic phenotype-predominant women with PCOS was not adequately evaluated. Objective: To assess the association of lipid profiles among metabolic phenotypes [body mass index (BMI) and insulin resistance (IR)] between women with and without PCOS. Methods: This case-control study included 287 reproductive-aged females with PCOS and 190 age-matched controls conveniently sampled from the PCOS clinic, Department of Endocrinology of a University hospital, between September 2020 and August 2022. The fasting glucose, insulin, and lipid profiles were analyzed using glucose oxidase, chemiluminescence immunoassay, and glycerol phosphate dehydrogenase peroxidase methods. LDL cholesterol was calculated from Friedwald’s formula or measured directly. The National Cholesterol Education Program’s risk categories for different lipid fractions in Adult Treatment Panel III were used. Participants were divided into lean (<23 kg/m2), overweight (23 – 27.4 kg/m2), and obese (≥27.5 kg/m2) by BMI, and IR by homeostasis model assessment of insulin resistance (HOMA-IR) ≥2.6. Results: Approximately 70.7% of women with PCOS had at least one abnormality in their lipid profile. Among all lipid fraction classifications, only the high-risk LDL-cholesterol category showed a significant association with PCOS after adjustment for BMI and HOMA-IR status [OR=9.2, p=0.041]. Different lipid fractions differed between the study groups only in the lean-overweight and insulin-sensitive groups. However, none of the diagnostic features, including phenotypes, had significant associations with lipid fraction categories. Conclusions: Only LDL cholesterol had an independent association with PCOS. An association between lipid fractions and PCOS was observed among women without obesity or IR. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 12-20]